PENGEMBANGAN PRODUKSI PUPUK ORGANIK KAYA Mg (PUPUK PEMANIS BUAH) - Witariadi, N.M; Kusmiyarti, Tati Budi; Putri, Budi Rahayu Tanama (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Activities aimed at developing the production of organic fertilizer to increase the Mg-rich sweet taste of fruit. Methods of execution include: raw materials, production and production processes. Raw materials such as chicken manure, mineral kiserit and wine dregs. Products produced in the form of organic fertilizer rich in mineral magnesium (Mg). The production process starts from the supply of raw materials, development of science and technology fertilizer production (fermentation), quality control (product analysis) and packaging. The results of activities in the form of organic fertilizer rich in mineral magnesium (Mg) to increase the sweetness in the fruit. Results of laboratory analysis of the nutrient content is obtained as follows: C / N = 12%, pH: 6.90, 14% organic C: 2.90% N, 2.37% P2O5, 1.39% K2O and Mg 22 58%. It is concluded that the development of Mg-rich organic fertilizer production adapted to the requirements and quality of organic fertilizer in Indonesia.